2022
DOI: 10.3390/genes13081331
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Single-Step GWAS Identifies Genes Influencing Fillet Color in Rainbow Trout

Abstract: The visual appearance of the fish fillet is a significant determinant of consumers’ purchase decisions. Depending on the rainbow trout diet, a uniform bright white or reddish/pink fillet color is desirable. Factors affecting fillet color are complex, ranging from the ability of live fish to accumulate carotenoids in the muscle to preharvest environmental conditions, early postmortem muscle metabolism, and storage conditions. Identifying genetic markers of fillet color is a desirable goal but a challenging task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…This discrepancy might be due to differences in the design of the two experiments, i.e., absence of supplemental Astaxanthin in one group of fish in Schmeisser et al [ 22 ] compared to our study, where both the white and red fillet groups were fed supplemental Astaxanthin. Retinol dehydrogenase-7 was identified in a genome-wide association study as one of the genes influencing fillet color in rainbow trout [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy might be due to differences in the design of the two experiments, i.e., absence of supplemental Astaxanthin in one group of fish in Schmeisser et al [ 22 ] compared to our study, where both the white and red fillet groups were fed supplemental Astaxanthin. Retinol dehydrogenase-7 was identified in a genome-wide association study as one of the genes influencing fillet color in rainbow trout [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species and oxidative stress can deteriorate lipids, adversely affecting fillet color [ 83 , 84 ]. A GWAS study identified several genes involved in myoglobin homeostasis and protection against lipid oxidation influencing fillet color in rainbow trout [ 5 ]. Such genes include cytochrome b5, ATP synthase subunit β, mitochondrial (ATP5F1B), calsequestrin, peroxiredoxin, superoxide dismutase, sestrin, and ubiquitin carboxyl-terminal hydrolase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation